Using chorographic sources to reconstruct past agro-forestry systems. A methodological approach based on the study case of the northern Apennines. (2nd April 2020) - Pezzi, Giovanna; Donati, Davide; Muzzi, Enrico; Conedera, Marco; Krebs, Patrik
ABSTRACT: Historical-geographical (chorographic) descriptions provide some of the earliest formal documentation about landscape. We propose a methodological approach aimed at reconstructing a spatial-explicit picture of the agroforestry system of a eighteenth-century landscape, detecting the main land-use drivers, and analysing existing legacies of past agro-forestry productivity in the present landscape. The study area was the Bologna Apennines, and our data source was a chorographic dictionary from 1781–83. We obtained a matrix of 240 administrative units per 18 agro-forestry products with related productivity indices. Multivariate analysis showed that environmental constraints influenced products and productivity. Agricultural areas (and related products) mainly shaped the hillside, while forests and semi-natural areas (and related products) characterized the mountainside. Such former clustering is still recognizable: agricultural land mostly changed to artificial land-cover, whereas semi-natural areas and forests still exist. The proposed approach confirms that chorography can be a useful tool as a primary source in landscape research.